The Tattoo Artist - Scheuermann, Silke, 1973- (Book collections on Project MUSE., 2019)
Drawn from Hong Kong International Poetry Nights 2011, The Tattoo Artist is a chapbook of poetry by Silke Scheuermann, accompanied by English and Chinese translations. The Tattoo Artist is also available along with the works of other internationally renowned poets in Words and the World (Twenty-volume Set). Selected poems from this volume are featured in the anthology Words and the World: International Poetry Nights in Hong Kong.